Adams-Bashforth methods on bigeometric calculus - Yilmazer, Mehmet Cagri; Goktas, Sertac; Yilmaz, Emrah; Et, Mikail (Amer Inst Mathematical Sciences-Aims, 2025)
In this study, bigeometric Adams-Bashforth methods were defined as a strong alternative to classical numerical methods. After methods were established theoretically, error estimation formulas for each method were developed. Finally, a classical differential equation was converted to a bigeometric multiplicative differential equation, and it was solved by using bigeometric AdamsBashforth methods. Then, error estimations were given.
Keywords: multiplicative calculus; bigeometric Adams-Bashforth methods; error estimation